2019
DOI: 10.1021/acsami.9b07500
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Matrix Membranes Formed from Imide-Functionalized UiO-66-NH2 for Improved Interfacial Compatibility

Abstract: Mixed-matrix membranes (MMMs) formed by dispersing metal–organic framework (MOF) particles in polymers have attracted significant attention because these composite systems can potentially surpass the separation performance of pure polymers alone. However, performance improvements are often unrealized because of poor interfacial compatibility between the MOF and the polymer, which results in interfacial defects. From a practical perspective, strategies are needed to address these defects so that MMMs can be dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 51 publications
4
109
0
Order By: Relevance
“…MOFs have been proven to have a higher affinity with organic polymer matrices with respect to zeolites, given the organic nature of the linkers that connect the metal clusters to one another [30]. Nevertheless, different strategies have been developed to further increase the interfacial compatibility between the components of MOF-based MMMs [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been proven to have a higher affinity with organic polymer matrices with respect to zeolites, given the organic nature of the linkers that connect the metal clusters to one another [30]. Nevertheless, different strategies have been developed to further increase the interfacial compatibility between the components of MOF-based MMMs [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, to improve the interfacial compatibility in MOF‐based mixed matrix membranes (MMMs), the most pursued approach is to covalently anchor functional moieties to a reactive group such as ‐NH 2 , ‐OH, ‐N 3 , or ‐COOH native to the MOF structure [20, 27–31] . The strong linkage between the polymer and the MOF reduces the possibility of interfacial separation thereby avoiding defect formation in the membrane [20, 32–35] . Nevertheless, many MOFs do not possess suitable reactive functional groups for grafting thus limiting the extended application of this method.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the hybridization method seems to be the most attractive to many researchers since respective superior features of both polymer matrix and filler materials can be well retained, including the easy processability and mechanical integrity of PVA and the flexible selection of the type and loading of porous fillers 16–18 . Furthermore, the addition of porous fillers can not only alter the bulky matrix microstructure of PVA but also influences the hydrophilic feature of PVA hybrids, subsequently affecting the film separation performance 16,18,19 . For example, Deng et al 20 have reported a non‐drying, water‐based method to fabricate a high‐quality ZIF‐8 (39 wt%)/PVA hybrid film for the dehydration of an ethanol/water mixture (90:10 in wt%) at 25°C and they found that compared to the permeability of 5.64 × 10 −5 cm 3 ·cm/(cm 2 ·s·kPa) and separation factor of 543 for the neat PVA film, the hybridization has greatly promoted both values, respectively, to 1.56 × 10 −4 cm 3 ·cm/(cm 2 ·s·kPa) and 4725.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier works, 10,11 the embedded zeolites of ZSM‐5 and Hβ into PVA have greatly boosted pervaporation separation selectivity and retained permeance for the isopropanol dehydration, probably due to the favorable hydrophilic and rigid porous features of zeolite as verified by the results of swelling and water contact angle tests. All these works tend to suggest, the embedded porous fillers must maintain a proper balance between hydrophilicity and hydrophobicity for successful dehydration performances 19,21 . Therefore, it is of great significance to explore the interfacial properties of the hybrid films so as to better understand the resultant separation performance.…”
Section: Introductionmentioning
confidence: 99%